Quantitative Assessment of Knee Progression Angle During Gait in Children With Cerebral Palsy. Issue 4 (April 2018) - Davids, Jon R.; Cung, Nina Q.; Pomeroy, Robin; Schultz, Brooke; Torburn, Leslie; Kulkarni, Vedant A.; Brown, Sean; Bagley, Anita M.
Abstract : Background: Abnormal hip rotation is a common deviation in children with cerebral palsy (CP). Clinicians typically assess hip rotation during gait by observing the direction that the patella points relative to the path of walking, which is referred to as the knee progression angle (KPA). Two kinematic methods for calculating the KPA are compared with each other. Video-based qualitative assessment of KPA is compared with the quantitative methods to determine reliability and validity. Methods: The KPA was calculated by both direct and indirect methods for 32 typically developing (TD) children and a convenience cohort of 43 children with hemiplegic type CP. An additional convenience cohort of 26 children with hemiplegic type CP was selected for qualitative assessment of KPA, performed by 3 experienced clinicians, using 3 categories (internal, >10 degrees; neutral, −10 to 10 degrees; and external, >−10 degrees). Results: Root mean square (RMS) analysis comparing the direct and indirect KPAs was 1.14+0.43 degrees for TD children, and 1.75+1.54 degrees for the affected side of children with CP. The difference in RMS among the 2 groups was statistically, but not clinically, significant ( P= 0.019). Intraclass correlation coefficient revealed excellent agreement between the direct and indirect methods of KPA for TD and CP children (0.996 and 0.992, respectively; P <0.001). For the qualitative assessment of KPA there was complete agreement among all examiners for 17 of 26 cases (65%). Direct KPA matched for 49 of 78 observations (63%) and indirect KPA matched for 52 of 78 observations (67%). Conclusions: The RMS analysis of direct and indirect methods for KPA was statistically but not clinically significant, which supports the use of either method based upon availability. Video-based qualitative assessment of KPA showed moderate reliability and validity. The differences between observed and calculated KPA indicate the need for caution when relying on visual assessments for clinical interpretation, and demonstrate the value of adding KPA calculation to standard kinematic analysis. Level of Evidence: Level II—diagnostic test.